1988
DOI: 10.1038/hdy.1988.92
|View full text |Cite
|
Sign up to set email alerts
|

New African species in the Drosophila obscura species group: genetic variation, differentiation and evolution

Abstract: The Drosophila obscura species group was known in the Afrotropical region from a single species, D. microlabis. This species was recently rediscovered in Kenya in addition to the discovery of three new obscura group species: D. kirumensis, D. cariouae and D. krimbasi. The patterns of allozyme variation in two African species, D. microlabis and D. kitumensis is compared to that of nine species of the obscura group. Genetic distances have been estimated from allelic frequencies at 35 loci and phylogenies inferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
0
4

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 35 publications
(18 reference statements)
9
36
0
4
Order By: Relevance
“…A similar disposition is also found in Loukas et al (1984). The tree of Cariou et al (1988) groups together all species of the subobscura cluster, but not in the right order; the position of the African species is between the branches of D. tristis and D. ambigua. D. tristis is the one closely related to D. obscura and this last is directly connected to the subobscura cluster.…”
Section: Discussionmentioning
confidence: 58%
“…A similar disposition is also found in Loukas et al (1984). The tree of Cariou et al (1988) groups together all species of the subobscura cluster, but not in the right order; the position of the African species is between the branches of D. tristis and D. ambigua. D. tristis is the one closely related to D. obscura and this last is directly connected to the subobscura cluster.…”
Section: Discussionmentioning
confidence: 58%
“…This microlabis-subobscura clade is nested within a larger Old World clade, which contains the remaining species placed in the obscura subgroup. Support for this hypothesis comes from biogeographic information (Throckmorton, 1975), previous morphological and molecular studies (Lakovaara and Saura, 1982;Cariou et al, 1988;Ruttkay et al, 1992), and cladistic analyses (Fig. 6 and data not shown).…”
mentioning
confidence: 93%
“…The common ancestor of these species groups likely colonized the western Nearctic region prior to mid-Miocene times, approximately 20 million years ago (Throckmorton, 1975). Recent expeditions in sub-Saharan Africa (Tsacas et al, 1985;Cariou et al, 1988) have discovered an additional subgroup, microlabis, which is found exclusively in the Afrotropical region (Fig. 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila subobscura, D. guanche and D. madeirensis are closely related species that form a cluster which differs from the other Drosophila species of the obscura group Cariou et al, 1988;Brehm & Krimbas, 1990;Gonzalez et al, 1990). In a previous work (Moltó et al, 1988) we compared the gene activity of D. subobscura and D. guanche throughout pre-pupal development, establishing that the latter species is less active.…”
Section: Introductionmentioning
confidence: 99%